Surgical management of the grade C pancreatic fistula after pancreatoduodenectomy. Issue 9 (September 2019) - Wroński, Marek; Cebulski, Włodzimierz; Witkowski, Bartosz; Guzel, Tomasz; Karkocha, Dominika; Lech, Gustaw; Słodkowski, Maciej
Abstract: Background: Surgical management of severe pancreatic fistula after pancreatoduodenectomy remains challenging, and carries high mortality. The aim of this retrospective study was to compare different surgical techniques used at relaparotomy for pancreatic fistula after pancreatoduodenectomy, and to identify factors predictive of failure to rescue. Methods: A total of 43 patients after pancreatoduodenectomy developed a pancreatic fistula requiring relaparotomy. The perioperative data and outcomes were reviewed retrospectively. Results: Completion pancreatectomy, simple drainage of the pancreatic anastomosis and external wirsungostomy were performed in 17, 16, and 10 cases, respectively. The mortality rate for completion pancreatectomy was 47.1%, compared with 56.3% for simple drainage (p = 0.598) and 50.0% for external wirsungostomy (p = 0.883). Simple drainage was associated with a higher rate of further relaparotomies (56.3%) in comparison with completion pancreatectomy (23.5%, p = 0.055) and external wirsungostomy (0%, p = 0.003). A rescue resection of the pancreatic remnant after failed simple drainage resulted invariably in death. On multivariate analysis, the factors predictive of mortality after relaparotomy for pancreatic fistula were organ failure on the day of reoperation (p = 0.001) and need of further surgical reintervention (p = 0.007). Conclusion: Timely reintervention and appropriate surgical technique are essential for reducing mortality after reoperation for pancreatic fistula after pancreatoduodenectomy.